2006
DOI: 10.1177/154405910608500416
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Endodontic Treatments on the Rigidity of the Root

Abstract: The destabilizing effect of endodontic treatment upon teeth is still controversial. The purpose of this study was to investigate the effects of different steps of endodontic treatments upon the rigidity of teeth. Extracted untreated central maxillary anterior teeth were loaded (3.75 N), and deformations of the root were assessed by Speckle pattern interferometry. The following treatments (with subsequent determination of deformability) were conducted sequentially: access preparation, manual instrumentation (Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
122
0
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(134 citation statements)
references
References 15 publications
5
122
0
7
Order By: Relevance
“…preparation reduces the rigidity of the tooth, 1 a tooth with a large loss of tooth structure generally requires a post-and-core foundation to provide restoration retention. 2 To avoid possible operational errors during post space preparation, 3 an alternative approach without use of endodontic posts, described as an endo-crown, was introduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…preparation reduces the rigidity of the tooth, 1 a tooth with a large loss of tooth structure generally requires a post-and-core foundation to provide restoration retention. 2 To avoid possible operational errors during post space preparation, 3 an alternative approach without use of endodontic posts, described as an endo-crown, was introduced.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental lithia disilicate ceramic crowns were made and adhesively cemented (Variolink). All teeth were subjected to thermal cycling and mechanical loading (TCML) in a masticator (1,200,000 loads, 49 N, 1.7 Hz, 3000 temperature cycles of 5°C-50°C-5°C). Marginal continuity was evaluated with scanning electron microscopy at ×200.…”
mentioning
confidence: 99%
“…Conversely, instrumentation that leads to irregular dentine removal with canal straightening will significantly weaken the root. 78 Lam et al 79 found a lower susceptibility to fracture in roots prepared with rotary NiTi instruments compared to those prepared by hand instrumentation, and believed that this difference was due to the rounder canal shapes produced by rotary files leading to fewer stress concentration sites. Collectively, the evidence indicates that apical enlargement with rotary NiTi instruments does not weaken roots any more than conventional hand instrumentation and may in fact increase fracture resistance.…”
Section: Size Of the Apical Preparationmentioning
confidence: 99%
“…According to (29) access cavity preparations in sound maxillary central incisors affects tooth stiffness by only 5%, and the removal of dentin at the wall of the canal without extensive alteration of the root canals' outline by manual widening resulted in minimal tooth deformation when using a light force. In fact, the largest reduction in tooth stiffness results from excessive access preparation, especially the loss of marginal ridges (30).…”
mentioning
confidence: 99%